HUBUNGAN KEMAMPUAN LITERASI SISWA DENGAN HASIL BELAJAR BIOLOGI DI SMA NEGERI 1 LABUHAN DELI - Irma Pratiwi; Idramsa Idramsa (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2019)
This research aims to determine student literacy skills in SMA Negeri 1 Labuhan Deli T.P 2017/2018 and the relationship of literacy skills of students with the result of the biology subject in SMA Negeri 1 Labuhan Deli T.P 2017/2018. The population is all of students in X MIA and XI MIA SMA Negeri 1 Labuhan Deli T.P 2017/2018.The total population is 200 people. The sample is determined by Random Sampling, where a sample of 67 people. This research is a quantitative approach with a correlational method. The data collection tool used was a literacy skills questionnaire and cognitive biology test. From the results of the data requirements test it is known that students' literacy abilities and result of biology subject was distributed normally and homogeneous with an average score of 98.82 and a standard deviation of 13.359 for student literacy skills data, and an average value of 61.88 with a standard deviation of 14.807 for result of biology subject The results showed that students' literacy skills in SMA Negeri 1 Labuhan Deli T.P 2017/2018 were good and there was a significant positive relationship between literacy skills of students and result of biology subject in SMA Negeri 1 Labuhan Deli T.P 2017/2018. This is evidenced by the correlation value of 0.269 and a significant value of 0.028 (p <0.05) at a significance level of 5%. The conclusion that the better the students' literacy skills, the better the result of biology subject at SMA Neegeri 1 Labuhan Deli.